Encapsulation Process of Propolis Extract by Casein Micelle Improves Sunscreen Activity - Sahlan, Muhamad; Dienayati, Dara; Hamdi, Darul; Zahra, Soraya; Hermansyah, Heri; Chulasiri, Malyn (Makara Journal of Technology, 2017)
Propolis, a wax bee glue, have antioxidant activity and effective as broad spectrum UVB and UVA photoprotection sunscreens agent. To improve photoprotection activity in sunscreen cream, the propolis was encapsulated by casein micelle. The Indonesian propolis was extracted by ethanol and separated the wax by freeze precipitation. The extract was encapsulated by casein and reduced their size by ball mill homogenizer with the encapsulation efficiency about 80% and size of particles about 80 nm. The particles was applied in sunscreen cream, evaluate their stabillity and photoprotection activity Sun Protection Factor (SPF) spectrophotometer (Optometric 290s). The results shows that the selected creams were stable and have moderate photoprotection activities higher than the controls. The encapsulation process of propolis by casein micelle can improve their photoprotection activity.